Indicators Of The Home Environment In Families At Risk Of Stunting In The Murai Valley Of Pontianak City - Widya Eka Lestari; Elly Trisnawati; Indah Budiastutik; Marlenywati, Marlenywati (Sean Institute, 2024)
Stunting is a serious nutritional problem that Indonesia is still facing. One of the cities in West Kalimantan Province that still contributes to stunting cases is Pontianak City, which is the provincial capital. The condition of environmental factors that are not optimal, supported by the characteristics of slum and densely populated areas, makes Pontianak City, especially the Murai Valley, an area that is vulnerable to stunting risks. This study aims to analyze the indicators of the home environment in families at risk of stunting in the Murai Valley, Pontianak City. The research design used is descriptive observational with a cross-sectional approach, the number of samples is 58 respondents who are categorized as Families at Risk of Stunting. Sampling was carried out by simple random sampling. The location of the research is in the Murai Valley Quality Family Village, Mariana Village, Pontianak City. Data were collected through interviews and direct observations, consisting of variables such as personal hygiene, cleanliness of the home environment, and cleanliness of latrines. The data was analyzed univariate and presented in the form of tables and narratives. The results of the study showed that the personal hygiene of families at risk of stunting was mostly 91.4% in the poor category. The cleanliness of the home environment was not clean by 62.1%, and as many as 93.1% of respondents described the cleanliness condition of the latrines as less qualified. There is a need to improve sanitation, cleanliness of the home environment and improvements to family toilet facilities. It is also hoped that there will be awareness of families at risk of stunting related to the implementation of clean and healthy living behaviors in the family order as a form of stunting prevention efforts.